2015
DOI: 10.1634/theoncologist.2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Induced Neurotoxicity and Preventive Strategies: Past, Present, and Future

Abstract: Neurotoxicity is a burdensome side effect of platinum-based chemotherapy that prevents administration of the full efficacious dosage and often leads to treatment withdrawal. Peripheral sensory neurotoxicity varies from paresthesia in fingers to ataxic gait, which might be transient or irreversible. Because the number of patients being treated with these neurotoxic agents is still increasing, the need for understanding the pathogenesis of this dramatic side effect is critical. Platinum derivatives, such as cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
160
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(170 citation statements)
references
References 201 publications
(251 reference statements)
4
160
0
6
Order By: Relevance
“…Using electrophysiological techniques, peripheral nerve changes are diagnosed as mononeuropathies such as carpal tunnel syndrome or mild to severe sensory and sensorimotor polyneuropathies of axonal origin. Studies suggest that the neurotoxic effects are triggered by drug accumulation in the dorsal root ganglia, causing neuronal dysfunction and apoptosis, thus leading to long‐term, often, irreversible changes in the peripheral nervous system (Avan et al., 2015; Park et al., 2015). …”
Section: Platinum‐based Drugsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using electrophysiological techniques, peripheral nerve changes are diagnosed as mononeuropathies such as carpal tunnel syndrome or mild to severe sensory and sensorimotor polyneuropathies of axonal origin. Studies suggest that the neurotoxic effects are triggered by drug accumulation in the dorsal root ganglia, causing neuronal dysfunction and apoptosis, thus leading to long‐term, often, irreversible changes in the peripheral nervous system (Avan et al., 2015; Park et al., 2015). …”
Section: Platinum‐based Drugsmentioning
confidence: 99%
“…These symptoms usually occur 30–60 min post infusion and resolve within a couple of days (Argyriou et al., 2013; Avan et al., 2015). The mechanisms underlying these transient neurotoxic effects remain unclear; however, recent studies indicate that they might be a direct result of structural properties of oxaliplatin.…”
Section: Platinum‐based Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35) The dysfunction of ion channels and apoptosis caused by a dysfunction of the mitochondria are considered to be possible etiologies for neurotoxicity. 36) Podratz et al reported that cisplatin, a derivative of l-OHP, inhibited mtDNA replication and induced mitochondrial degradation in vitro and in vivo. 37) As such, the mechanism for mitochondrial toxicity appears not to be specific to neuronal cells, and could also be a cause of toxicity in Kupffer cells.…”
Section: 71×10mentioning
confidence: 99%